1985
DOI: 10.1161/01.res.57.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Neuronally released norepinephrine does not preferentially activate postjunctional alpha 1-adrenoceptors in human blood vessels in vitro.

Abstract: Human isolated digital arteries and metatarsal veins, obtained postmortem, have been used to compare the effects of alpha-adrenoceptor antagonists on contractile responses to nerve stimulation. The antagonists used were prazosin, rauwolscine, BE 2254, and yohimbine. Rauwolscine (alpha 2-antagonist), as well as prazosin and BE 2254 (alpha 1-antagonists), in concentrations of 10(-9), 10(-8), and 10(-7) mol/liter, potently antagonized the frequency-response curves to nerve stimulation. Yohimbine (alpha 2-antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Later results from investigations on human isolated resistance arteries disputed this hypothesis, indicating that both a 1 -and a 2 -adrenoceptors are activated postjunctionally by neurally released NA (Stevens & Moulds, 1985;Parkinson et al, 1992;Stephens et al, 1992). Recently, we observed that both a 1 -and a 2 -adrenoceptors contributed to the vasoconstrictor responses to exogenously applied NA in human isolated, perfused gastroepiploic arteries (Fukui & Chiba, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Later results from investigations on human isolated resistance arteries disputed this hypothesis, indicating that both a 1 -and a 2 -adrenoceptors are activated postjunctionally by neurally released NA (Stevens & Moulds, 1985;Parkinson et al, 1992;Stephens et al, 1992). Recently, we observed that both a 1 -and a 2 -adrenoceptors contributed to the vasoconstrictor responses to exogenously applied NA in human isolated, perfused gastroepiploic arteries (Fukui & Chiba, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…The neurogenic vasoconstrictor response to LBNP is influenced by both the amount ofNE released from sympathetic nerves (facilitated by prejunctional beta receptor stimulation) and by the vascular responsiveness to neurally released NE. Both the neurally released and the exogenous NE stimulate postjunctional alpha-l and alpha-2 vascular adrenoceptors equally (24,25). The vascular responses to the neurally released NE could have been altered during the course of these experiments by postjunctional effects of isoproterenol and epinephrine and by changes in resting FVR.…”
Section: (I) Experimental Designmentioning
confidence: 99%
“…A comparative study by Nielsen et al (1991) examined the pharmacological characteristics of x-adrenoceptor-mediated contractions to noradrenaline in similar sized mesenteric arteries (200 fym diameter) from the rat, rabbit, pig and man and found a2-adrenoceptor-mediated contractions detectable only in porcine and human blood vessels. Further, there are reports that indicate that ml-and a2-adrenoceptors participate in sympathetically mediated vasoconstriction of human vessels (Stevens & Moulds, 1985;Parkinson et al, 1992), yet a-adrenoceptor mediated constrictor responses in small arteries from the rat, guinea-pig and rabbit appear to be exclusively via al-adrenoceptors (Angus et al, 1988;McGrath et al, 1989). It seems likely that in small mammals, neuronally activated x2-adrenoceptors reside on blood vessels too small for routine experimentation (see Ohyanagi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%